Transapical aortic valve implantation in 100 consecutive patients: comparison to propensity-matched conventional aortic valve replacement - Walther, Thomas; Schuler, Gerhard; Borger, Michael Andrew; Kempfert, Joerg; Seeburger, Jörg; Rückert, Yvonne; Ender, Joerg; Linke, Axel; Scholz, Markus; Falk, Volkmar; Mohr, Friedrich Wilhelm (European heart journal, 2010)
AIMS\backslashr\backslashnTo evaluate the outcome of transapical aortic valve implantation (TA-AVI) in comparison to conventional surgery.\backslashr\backslashnMETHODS AND RESULTS\backslashr\backslashnOne hundred consecutive high-risk patients with symptomatic aortic valve stenosis received TA-AVI using the Edwards SAPIEN pericardial xenograft between February 2006 and January 2008. Patient age was 82.7 +/- 5 years, 77 were females, logistic EuroSCORE predicted risk of mortality was 29.4 +/- 13% and Society Thoracic Surgeons score risk for mortality was 15.2 +/- 8.3%. Propensity score analysis was used to identify a control group of patients that underwent conventional aortic valve replacement (C-AVR). Transapical aortic valve implantation was performed successfully in 97 patients, whereas three patients required early conversion. There were no new onset neurological events in the TA-AVI group and early extubation was performed in 82 patients. Echocardiography revealed good valve function with low transvalvular gradients in all patients. Thirty-day survival was 90 +/- 3 vs. 85 +/- 4% for TA-AVI vs. C-AVR, and 1-year survival was 73 +/- 4 vs. 69 +/- 5% (P = 0.55).\backslashr\backslashnCONCLUSION\backslashr\backslashnTransapical aortic valve implantation is a safe, minimally invasive, and off-pump technique to treat high-risk patients with aortic stenosis. Results of the initial 100 patients are good and compare favourably to conventional surgery.